Sampled-Data Consensus of Multi-Agent System in the Presence of Packet Losses - Xin Wang; Hui Wang; Junjian Huang; Jurgen Kurths (IEEE Access)
The consensus problem is investigated in this paper for multi-agent systems subjected to sampled data and packet losses. The switching system, which simultaneously contains both stable and unstable subsystems, is applied to model the packet dropout in a deterministic way. The focus of this paper is to derive an improved condition stated elegantly in terms of linear matrix inequality (LMI) with less conservative and lower complexity such that the multi-agent system considered can reach consensus. In line with this, a novel nonlinear function is introduced in the construction of the piecewise differentiable Lyapunov functions, and the Wirtinger inequality is applied as well. Furthermore, several comparison results against other related ones are presented, which yield that our consensus protocols significantly improve upon the existing ones advocated thus far. We verify the validity, the effectiveness, and the practical applicability of our results in the simulation examples.